Immersion Time and Annealing Temperature Effect on TiO2 Thin Films Deposited by Hydrothermal Method - Al-Jawad, Selma M. H; Mohammad, Mohammad R; Imran, Natheer Jamal (Al-Nahrain Journal of Science, 2017)
In this work, TiO2 nanofibers thin films were prepared by using different immersion times for hydrothermal method. Annealing in air at different temperatures of (400,500, and 600)°C at constant time (1 hour) were achieved for all films. Many analysis and measurement had been done (XRD, SEM, EDX, and AFM), and optical (UV-Visible spectroscopy, PL spectroscopy, and Spectral Response). The properties of nanofibers TiO2 films were investigated and analyzed for films. The SEM analysis of TiO2 films showed nanofibers shapes with diameter of about 21 nm. The absorption edges are located at UV-region, and the Eg has higher values compared with Eg for bulk TiO2 film. Spectral response measurements show photocurrent peaks for TiO2 nanotube films centered at UV-region (350 nm).